ANALISIS SEBARAN PERGERAKAN KOMODITAS KOPI DI PROVINSI JAWA BARAT - Situmeang, Steven Julianto; Akbardin, Juang; Ramadhansy , Luthfia Rizky; Wulansari, Dwi Novi (Berkala Forum Studi Transportasi antar Perguruan Tinggi, 2024)
In 2019, the coffee commodity was in the first place for most exports in the Indonesian agricultural sector. This makes coffee one of the largest foreign exchange earning commodities for Indonesia. In this scientific article, we will discuss the movement of the distribution of coffee commodities through multimodal transportation in West Java Province. The zones to be reviewed are Sukabumi, Cianjur, Garut, Tasikmalaya, Ciamis, Kuningan, Majalengka, Sumedang, Subang, Purwakarta and Karawang. The method used for the analysis of the distribution of movement in this study is the unrestricted gravity model (UCGR), where the primary data is obtained from the results of data processing that the researchers did and the secondary data is obtained from a literature review that is relevant to the topic discussed. After analyzing the distribution of coffee in the eleven zones reviewed, the appropriate types of transportation modes, transport capacity, BOK, and MAT of the distribution of coffee commodities in West Java were obtained. ABSTRAK Pada tahun 2019, komoditas kopi menduduki urutan pertama paling banyak diekspor di sektor pertanian Indonesia. Hal tersebut menjadikan kopi sebagai salah satu komoditas penyumbang devisa terbesar bagi Indonesia. Pada artikel ilmiah ini, akan dibahas mengenai pergerakan persebaran komoditas kopi melalui transportasi multimoda di Provinsi Jawa Barat. Zona yang akan ditinjau adalah Sukabumi, Cianjur, Garut, Tasikmalaya, Ciamis, Kuningan, Majalengka, Sumedang, Subang, Purwakarta, dan Karawang. Metode yang digunakan untuk analisis sebaran pergerakan pada kajian ini adalah model gravity tanpa-batasan (UCGR), dimana data primer didapatkan dari hasil pengolahan data yang peneliti lakukan dan data sekunder didapat dari tinjauan literatur yang relevan dengan topik yang dibahas. Setelah dilakukan analisis terhadap persebaran kopi di sebelas zona yang ditinjau, didapatkan jenis moda transportasi yang sesuai, kapasitas alat angkut, BOK, serta MAT distribusi pergerakan komoditas kopi di Jawa Barat.